2020
DOI: 10.1186/s12935-020-01515-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers and candidate small molecule drugs in glioblastoma

Abstract: Background and aims: Glioblastoma (GBM) is a common and aggressive primary brain tumor, and the prognosis for GBM patients remains poor. This study aimed to identify the key genes associated with the development of GBM and provide new diagnostic and therapies for GBM. Methods: Three microarray datasets (GSE111260, GSE103227, and GSE104267) were selected from Gene Expression Omnibus (GEO) database for integrated analysis. The differential expressed genes (DEGs) between GBM and normal tissues were identified. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Studies ( Mullee and Morrison, 2016 ; Semer et al, 2019 ) had shown that CEN2 was a transcriptional co activator, which could reshape the epigenetic landscape of promoters. In previous cancer research, it had received some attention as a potential biomarker ( Anurag et al, 2018 ; Lu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies ( Mullee and Morrison, 2016 ; Semer et al, 2019 ) had shown that CEN2 was a transcriptional co activator, which could reshape the epigenetic landscape of promoters. In previous cancer research, it had received some attention as a potential biomarker ( Anurag et al, 2018 ; Lu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that CETN2 is expressed in astrocytes of primary glioblastomas, in a stage of tumor progression which is, by definition, the most severe. Lu et al (2020) also reported that low CETN2 expression could be correlated to better survival of patients with GBM, thus suggesting that CETN2 expression increases with disease evolution. However, a more systematic investigation on lower grade astrocytomas would be needed to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…In GBM, channels involved in ionic transport have their expression frequently affected (Polisetty et al, 2012) and calcium concentration, in particular, has been demonstrated to be pivotal for tumor initiation, maintenance, and infiltration (Leclerc et al, 2016;Guan et al, 2018). Accordingly, the transcriptional profile of several genes coding for calcium-binding proteins, including CETN2, have their expression altered in GBM (Loh et al, 2010(Loh et al, , 2012Robil et al, 2015;Lu et al, 2020). Our results demonstrate that CETN2 is expressed in astrocytes of primary glioblastomas, in a stage of tumor progression which is, by definition, the most severe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that the changes in gene expression of various methyltransferases, acetyltransferases, and deacetylases promoted the pathogenesis of GBM 189 . The nuclear expression levels of lysine methyltransferases SETDB1, KMT5B, Suv‐39h1, and EZH2 in GBM are up‐regulated, compared with normal tissues, and correlated with advanced histological grades 190–193 . Besides, the inhibition of LSD1 in GBM has been discovered by Chandra et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 91%